2007
DOI: 10.1111/j.1440-1746.2007.05010.x
|View full text |Cite
|
Sign up to set email alerts
|

Highly endemic hepatitis B infection in rural Vietnam

Abstract: Hepatitis B virus infection is highly endemic in rural Vietnam. Poor infection control activities in health-care settings contribute to high HBV prevalence in this region. Universal HBV infant vaccination and improved infection control procedures are required for improved HBV control in Vietnam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
85
2
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 28 publications
(62 reference statements)
7
85
2
2
Order By: Relevance
“…Although we found HCV infection to be uncommon and our sample size provided a good degree of reliability for our prevalence rate, 1-2 per 100, a considerably larger population is needed before we can rule out as risk factors for HCV the remaining variables on which we collected data. Our original aim was to investigate the prevalence and risk factors for HBV infection, in a calculated sample size based on the expected HBV prevalence-a far more common occurrence requiring a smaller sample than that for HCV estimates [16]. Recall bias might have influenced our findings, but this would be nondifferential as participants were unaware of their sero-status at the time of their interview.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we found HCV infection to be uncommon and our sample size provided a good degree of reliability for our prevalence rate, 1-2 per 100, a considerably larger population is needed before we can rule out as risk factors for HCV the remaining variables on which we collected data. Our original aim was to investigate the prevalence and risk factors for HBV infection, in a calculated sample size based on the expected HBV prevalence-a far more common occurrence requiring a smaller sample than that for HCV estimates [16]. Recall bias might have influenced our findings, but this would be nondifferential as participants were unaware of their sero-status at the time of their interview.…”
Section: Discussionmentioning
confidence: 99%
“…This study population was then randomly selected using a systematic method. A more detailed description of the methodology and results of HBV testing has been published [16].…”
Section: Methodsmentioning
confidence: 99%
“…Our review found that the reported HBsAg prevalence in general population ranged from 5.7% to 24.7% in Vietnam, with most reporting the prevalence from 10% to 20%. 7,9,10,11,13,17,22 The value was much higher for the indicators of past infection: the anti-HBs ranged from 16% to 40% and anti-HBc from 50% to 75%. 22,10,13 There are an estimated 8.4 million people living with chronic hepatitis B in Vietnam.…”
Section: Overview-hepatitis B and C And Hiv Coinfection In Vietnammentioning
confidence: 99%
“…At present, the prevalence of HBV infection in Vietnam is more than 8%, and in some regions it may be up to 25% (1)(2)(3)(4). Vietnamese HBV strains share characteristics of mutations in the core promoter and enhancement II region of the X gene in its genome, similar to HBV strains from China, Hong Kong and Japan.…”
Section: Introductionmentioning
confidence: 99%